Thymidine phosphorylase in nucleotide metabolism: physiological functions and its implications in tumorigenesis and anti-cancer therapy - Huang, Bo; Yuan, Qihang; Sun, Jiaao; Wang, Chao; Yang, Dong (Frontiers in Immunology, 2025)
Thymidine phosphorylase (TYMP), a protein found in both prokaryotic and eukaryotic cells, is encoded by a gene located in the q13 region of chromosome 22. With a relative molecular mass of 55,000, TYMP exists as a homodimer. Recent research has increasingly illuminated the diverse functions of TYMP. It is known to facilitate platelet activation, osteoclast differentiation, and angiogenesis. Mutations in the TYMP gene are linked to mitochondrial neurogastrointestinal encephalomyopathy. Beyond its physiological roles, TYMP contributes significantly to tumor growth and cancer progression, where it promotes angiogenesis, modulates epigenetic genes, inhibits apoptosis, and acts as a critical enzyme in the nucleoside metabolic rescue pathway. Moreover, TYMP holds substantial implications in cancer treatment and prognosis. Given its involvement in cancer progression, TYMP inhibitors may prove valuable in inhibiting tumor growth and metastasis. Interestingly, while TYMP can drive tumor growth, certain concentrations of TYMP also enhance the cytotoxic effects of chemotherapy drugs such as 5-fluorouracil (5-FU). Although challenges exist—such as the potential disruption of normal physiological functions when inhibiting TYMP—the protein remains a promising target for cancer treatment. Ongoing research on TYMP could deepen our understanding of human physiology and the pathogenesis of cancer and open new avenues for therapeutic interventions. This article provides a comprehensive review of TYMP’s structure, physiological functions, and its role in tumorigenesis and anti-tumor therapy.